Comparative Clinical Trial of Fluoridated Varnishes with Calcium Compounds to Prevent and Reverse Incipient Carious Lesions in School Children - Adriana, Juarez-Lopez Maria Lilia; Miriam, Marin Miranda; Nelly, Molina Frechero (European Scientific Journal, ESJ, 2020)
Objective: This paper focuses on comparing the clinical effectiveness of two fluoridated varnishes enhanced with calcium compounds to prevent and reverse incipient carious lesions (ICL). Method: A clinical study was carried out with 156 children aged 7-9 years. They were distributed into three groups for the topical application of: a) a sodium fluoride varnish with caseinphosphopeptide-amorphous-calcium-phosphate (CPP-ACP/NaF); b) a sodium fluoride varnish with phosphate-tri-calcium (NaF-TCP); c) a control. The application were every six months Caries Protective fraction (PF) which was obtained from Epidemiological indexes. Also, 2594 dentalsurfaces with caries free and incipient caries lesions (ICL) were followed up after 18 months. ANOVA repeated measures were carried out, and McNemar and Gamma tests were also performed. Results: The DMFS values after treatments showed the following: a) 1.9± 4, b) 2.5± 2, and c) 3.1± 4.8 (p =0.17) with PF of 38% and 18% for groups CPP-ACP/NaF and NaF-TCP, respectively. ICL showed a reversal in 26.6% (IC95: 17-35) of the CPP-ACP/NaF group, 24.6% (IC95: 14-33) in the NaF-TCP group, and 23% (IC95: 13-32) in the control group.. The percentage of free caries and incipient caries teeth were higher for CPPACP/F than control group. p= 0.001. Conclusion: Varnishes with calcium compounds promoted the recovery of ICL. However, CPP-ACP/NaF showed a better protective factor.